2007
DOI: 10.1136/ip.2006.013359
|View full text |Cite
|
Sign up to set email alerts
|

Reducing firearm violence: a research agenda: Table 1

Abstract: In the United States, firearms are involved in tens of thousands of deaths and injuries each year. The magnitude of this problem prompted the National Academy of Sciences (NAS) to issue a report in 2004 detailing the strengths and limitations of existing research on the relationship between firearms and violence. In response, a multidisciplinary group of experts in the field of firearms and violence formed the National Research Collaborative on Firearm Violence. The Collaborative met for 2 days in June 2005 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…More specifically, controls were sampled from all of Philadelphia using random digit dialing (Waksberg, 1978; Weiner et al, 2007). The protocol allowed for controls who later were shot to remain eligible for inclusion in the study as cases (Rothman & Greenland, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, controls were sampled from all of Philadelphia using random digit dialing (Waksberg, 1978; Weiner et al, 2007). The protocol allowed for controls who later were shot to remain eligible for inclusion in the study as cases (Rothman & Greenland, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The National Research Collaborative on Firearm Violence recently observed that the accumulated evidence supports a causal relationship between the availability of firearms and suicide 10. In one of the most cited studies, Sloan et al 11 found that, although the risk of death from suicide in Seattle and Vancouver (British Columbia) did not differ significantly, the rate of firearm suicide was higher in Seattle (relative risk 2.3; 95% CI 1.9 to 2.9), where firearms are more available.…”
mentioning
confidence: 99%
“…These include violence prevention in low and middle-income countries,26 child abuse,22 27 28 occupational injuries,29 30 sexual violence,31 firearm-related injuries32 and farm injuries 33. These agendas have been supported in some cases by government institutions, professional organisations or academic institutions.…”
Section: Need For a Global Injury Research Agendamentioning
confidence: 99%